2014
DOI: 10.1186/1475-2840-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle markers in relation to obesity and metabolic complications in patients with manifest cardiovascular disease

Abstract: BackgroundAlterations in extracellular vesicles (EVs), including exosomes and microparticles, contribute to cardiovascular disease. We hypothesized that obesity could favour enhanced release of EVs from adipose tissue, and thereby contribute to cardiovascular risk via obesity-induced metabolic complications. The objectives of this study were: 1) to investigate the relation between the quantity, distribution and (dys) function of adipose tissue and plasma concentrations of atherothrombotic EV-markers; 2) to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 49 publications
7
81
0
3
Order By: Relevance
“…Thus the global analysis of circulating miRNAs might result in a complex signature that superimposed different miRNAs variations according to their mode of secretion. A recent study demonstrated that the level of some specific exosomal proteins was positively related to metabolic complications of obesity suggesting that concomitantly the level of specific exosomal miRNAs might also variate [82]. Therefore we suggest that it would be more appropriate to analyze each serum/plasma fractions independently (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the global analysis of circulating miRNAs might result in a complex signature that superimposed different miRNAs variations according to their mode of secretion. A recent study demonstrated that the level of some specific exosomal proteins was positively related to metabolic complications of obesity suggesting that concomitantly the level of specific exosomal miRNAs might also variate [82]. Therefore we suggest that it would be more appropriate to analyze each serum/plasma fractions independently (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46] However, in the prevailing literature, no study has investigated the interaction between adipocyte-derived EVs and the central nervous system (CNS). A, Differential MALAT1 expression in the adipose tissue and hypothalamus of obese and lean mice.…”
Section: F I G U R Ementioning
confidence: 99%
“…Validation of Differential Expression-In effort to cross-validate the expression levels of EVs obtained from PUC, ExoQuick™ (System Biosciences, Mountain View, CA), an alter- native method for EV precipitation, (80,81), was used to isolate plasma EVs from 17 MI patients and 26 NMI patients. In order to ensure the accuracy of label-free quantitation from the discovery study, established luminex assay and ELISA was used to validate the expression levels of the prospective candidate complement proteins (C1QA and C5), lipoproteins (APOD and APOC3) and platelet-associated proteins (GP1BA and PPBP), in 43 individual patient plasma samples (detailed concentration readings available in supplemental Data S4; worksheet LumCon).…”
Section: Fig 2 Verification Of the Identity Of Extracellular Vesiclmentioning
confidence: 99%